A nem kormányzati szervezetek Kenyában: A civil mozgalmak áttekintése 1991-től napjainkig - Solymári, Dániel; Mangera, Janet (Afrika Tanulmányok / Hungarian Journal of African Studies, 2020)
The role of African civic and non-governmental organizations has grown exponentially over the past ten years. Their number in Kenya has reached eleven thousand, with annual revenues in excess of one and a half billion dollars. However, the country has come a long way since the “difficult 1990s”, Kenya’s period of democratization. Fostering cooperation between NGOs and the government continues to have its problems, but without “civilians” there would be a huge gap in the field of development aid. In our article, we have reviewed the history and regulatory framework of the non-governmental sector in Kenya and its re-emergence.